(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
This study investigated the characteristics of environmental journalism in conjunction with data journalism, analyzing news articles and reports on climate change published between 2022 and 2023 by InfoAmazonia and ((o))eco. Based on an exploratory approach without predefined hypotheses, the research aimed to identify the specificities of this intersection, assess existing guidelines, and understand the challenges involved. Through content analysis, the study examined the relevance of these practices in the context of climate emergencies, considering their impact on the production of more in-depth and comprehensible reporting. The findings revealed that temporal and geospatial visualizations are crucial for addressing complex topics, although the choice of visualization formats must be aligned with communication objectives and the available data.